Simplified analysis of damage evolution in surface-damaged metallic strands: Uncoupled approach. (January 2022) - Beltrán, Juan Felipe; Inostroza, Exequiel
Highlights: Isotropic ductile damage evolution law is numerically assessed for surface-damaged metallic strands. Fracture energy-based criterion is interpreted using the damage homogenization approach. 1 × 7 strand damage state evolves to an unstable condition for a number of surface cut wires greater than two. Asymmetric surface cut wires distribution induces a faster decrease in strands capacity to develop ductile damage. Abstract: In this paper, an isotropic damage evolution law of initially intact and pre-damaged ductile metallic strands is assessed using a well-established uncoupled procedure that relies on the static tensile tests of the wires that form the strands and on a numerical algorithm to simulate pre-damaged strand response. The strands construction is 1 × 7 and their diameter values vary from 9.5 mm to 14.3 mm. Pre-damaged strands account for a prescribed number of surface wires cut in both symmetric and asymmetric patterns prior loading, which defines the initial damage level. A detailed discussion is provided regarding the effect of the initial damage pattern (symmetric or asymmetric) on the damage evolution law and damage critical values reached by the strands. Assuming a linear damage evolution for the wires, intact and pre-damaged strands possess increasing multilinear homogenized damage evolution laws. A discussion is provided on the interpretation of the damage index given by the uncoupled fracture energy-based criteria in terms of the strands damage evolution using a damage homogenization approach. Numerical results indicate that the maximum allowable number of surface cut wires is two considering both asymmetric and symmetric distributions. Greater number of cut wires induces that the strand damage state evolves to an unstable condition, evolution that is steeper for the asymmetric distribution case.